Accelerator or Brake: Immune Regulators in Malaria - Cai, Chunmei; Hu, Zhiqiang; Yu, Xiao (Frontiers in Cellular and Infection Microbiology, 2020)
Malaria is a life-threatening infectious disease, affecting over 250 million individuals worldwide each year, eradicating malaria has been one of the greatest challenges to public health for a century. Growing resistance to anti-parasitic therapies and lack of effective vaccines are major contributing factors in controlling this disease. However, the incomplete understanding of parasite interactions with host anti-malaria immunity hinders vaccine development efforts to date. Recent studies have been unveiling the complexity of immune responses and regulators against Plasmodium infection. Here, we summarize our current understanding of host immune responses against Plasmodium-derived components infection, and mainly focus on the various regulatory mechanisms mediated by recent identified immune regulators orchestrating anti-malaria immunity.